Thermographic evaluation of electro-mechanical relays’ quality in railway automation - Anna Vladova Andonova (International Journal of Electrical and Computer Engineering (IJECE), 2012)
By using thermal photography the quality of an electro-mechanical relay can be examined during production and the reliability of the series can be guaranteed at higher electric current values during commutation process. During exploitation thermal photography is provided information about the degree of wearing out of contacts and to help determine which contacts need to be replaced. By means of thermal photography the duration of gas discharge is determined and this duration is an indicator about the speed of wearing out of the contacts. The article offers a method to determine the quality of electro-mechanical relays especially developed for switching of powerful electrical circuits used in railway automation.Keywords: NDE, thermography, electromechanical relaysDOI:http://dx.doi.org/10.11591/ijece.v2i1.33